Recent progress on single atom/sub-nano electrocatalysts for energy applications. (January 2021) - Tran, Duy Thanh; Nguyen, Dinh Chuong; Le, Huu Tuan; Kshetri, Tolendra; Hoa, Van Hien; Doan, Thi Luu Luyen; Kim, Nam Hoon; Lee, Joong Hee
Graphical abstract: Highlight: Single atom/sub-nano catalysts (SACs/SNCs) have superior structure and properties. Recent progress in synthesis approaches for SACs/SNCs was highlighted. Relationship between structure and intrinsic properties of SACs/SNCs was explained. Electrochemical applications and prospective future of SACs/SNCs were discussed. Abstract: The development of low-cost and effective catalysts is highly necessary in the field of electrochemical applications. Recently, single atom and sub-nano catalysts (SACs and SNCs) have been emerging as excellent candidates due to their enriched active sites, extraordinary structural design, and unique electronic behavior. Therefore, the formation of well dispersed SACs and SNCs effectively stabilized on reasonable supports has been demonstrated as an advanced strategy to greatly improve the efficiency of catalytic processes. In addition, it also offered a wonderful opportunity to observe, study, and explain the mechanism of catalytic reactions at atomic scale. In this work, we comprehensively reviewed recent advances in state-of-the-art researches on the structures, properties, and applications of SACs and SNCs. The relationships between unique morphology/structures and intrinsic physicochemical properties of the catalysts were evaluated to further understand underlying reasons behind their advanced performance. Continuously, various potential electrochemical applications of SACs and SNCs were also emphasized in detail. Furthermore, some existing challenges in fundamental studies and practical applications, as well as forthcoming prospects for the development of SACs and SNCs were briefly discussed as well.